2018
DOI: 10.1111/jgs.15379
|View full text |Cite
|
Sign up to set email alerts
|

Health and Aging Policy Fellows: Dementia and Mental Health Policy to Improve Lives of Older Adults

Abstract: The Health and Aging Policy Fellows (HAPF) Program has, since its inception in 2008, provided health policy training and mentorship for 113 gerontological professionals across a wide range of disciplines and stages of careers. The fellows' shared passion is the effective engagement of policy levers to improve the lives of older adults. This article briefly describes the HAPF Program and provides a sample of policies with which fellows have been engaged related to dementia and late-life mental health. Approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The present study showed that mental health score increased with ageing. Previous studies revealed that general health declines with age, 47,48 and specific mental health disorders, seem to be more prevalent in younger highly educated people. 49 Mental health score in our academic physician's population was significantly lower in single female participants.…”
Section: Mental Health Determinants In Academic Physiciansmentioning
confidence: 96%
“…The present study showed that mental health score increased with ageing. Previous studies revealed that general health declines with age, 47,48 and specific mental health disorders, seem to be more prevalent in younger highly educated people. 49 Mental health score in our academic physician's population was significantly lower in single female participants.…”
Section: Mental Health Determinants In Academic Physiciansmentioning
confidence: 96%
“…Over a decade, more than 100 fellows have been trained on improving the implementation of geriatric care programs. 45 This cadre can be a source of advisory support over long periods. 45 , 46 A similar cadre would greatly benefit GMH policy planning and implementation.…”
Section: Future Directionsmentioning
confidence: 99%
“… 45 This cadre can be a source of advisory support over long periods. 45 , 46 A similar cadre would greatly benefit GMH policy planning and implementation.…”
Section: Future Directionsmentioning
confidence: 99%
“…An important outcome was the April 2018 supplemental issue of the Journal of the American Geriatrics Society (Stephens, Evans, Bradway, & Buckwalter, 2018) that includes four interprofessional white papers and accompanying brief commentaries encompassing science (Massimo, Kales, & Kolanowski, 2018;Gilmore-Bykovski, 2018;Manning & Steffans, 2018;Wright, 2018), practice (Callahan, et al, 2018;Sturdevant, 2018), education and training (Farrell, et al, 2018;Harris, 2018) and policy (Cacchione, Pike, Spaeth-Rublee, & Pincus, 2018). The invitational Think Tank included conference speakers and selected attendees (experts, stakeholders, emerging leaders/scholars in the field) who were asked to focus on three themes: Building the Science, Training Current & Future Generations, and Designing Practice Models.…”
Section: Progress In Advancing Gpn Leadership In Workforce Planning and Policy-makingmentioning
confidence: 99%